Diagnosing overtraining in athletes using the two-bout exercise protocol - Meeusen, R.; Nederhof, E.; Buyse, L.; Roelands, B.; de Schutter, G.; Piacentini, M. F. (British Journal of Sports Medicine, 2010)
Objective: In this work, whether a two-bout exercise protocol can be used to make an objective, immediately available distinction between non-functional over reaching (NFO) and overtraining syndrome (OTS) was studied.